SIFAT DAN KUALITAS GAHARU (GONYSTILLUS SPEC.) - Tjutju Nurhayati Syahri (Jurnal Penelitian Hasil Hutan, 1989)
Gaharu of  Gonystillus spec.  from  South  Kalimantan   has the following  properties   :   moisture  content   5%,  essential  oil content   51%,  caloriffic   value  5655  cal/g, ash content   0.24%,   and  specific  gravity  0. 76. According   to  the  quality   clasifi cation,  the gaharu  of  Gonystillus spec.  belong  to  no.  I -   b,  and  its sales was Rp.   250,000.-Lignin  content   of gaharu was about  the same as lignin content   of wood,  cellulose  and pentosan  are somewhat   lower.It  was meant  that  lignin  was not  be degradated,   but  cellulose  and pentosan   was degradated  by fungi  in the production of gaharu.